UKRAINIAN NATIONAL IDENTITY BETWEEN EUROPEAN VALUES AND "HOMO SOVIETICUS" HYBRID IDENTITY: SYNERGY OF UNCERTAINTY AND STIPULATIONS - Kononenko, T. (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2017)
Abstracts of papers [1] presented at the conference "The Contemporary Relations between Russia, Ukraine and the European Union. Conference at Landstingssalen, The Danish Parliament, Christansborg, Friday the 23 of January, 2015" [2].